The Sense-Making of Home Among Vietnamese Returning Graduates - Nguyen, Chi Hong (Journal of International Students, 2023)
While many Vietnamese students are reported to study abroad, experiences of home-making among Vietnamese returning students are paid scant attention to in current research on Vietnamese international student mobility. Conversations with 13 Vietnamese returning graduates were conducted in this study to explore the sense-making of home through a Heideggerian perspective on building and dwelling at home. The analysis of the empirical material shows that home which is constructed and experienced by the returning graduates’ use of intersecting materials is socially shared. It is an embodiment of returning migrants’ engagement in the world with familiarity and discomfort created by their friction with the interrelated materialistic and discursive aspects of life. Their returns involve incomplete life happenings with diverse emotions and experiences of belonging. The findings of this study add nuance to the extant understanding of home as belonging and challenge the common conceptualization of home as a private space.